CRISPR/Cas9-Mediated Editing in FAD2 Gene to Enhance Oil Quality in Soybean [Glycine max (L.) Merrill] - Balaji U. Rathod; Riddhi Rajyaguru; Ramesh N. Dhawale; Rukam S. Tomar; Shasikant Sharma; Manohar G. Chaskar; Omar Awad Alsaidan; Sunil Tulshiram Hajare (PLoS ONE, 2026)
Conventional soybean oil contains high levels of linoleic acid, which reduces oxidative stability and necessitates hydrogenation, leading to trans-fat formation. In this study, 40 Indian soybean genotypes were screened for fatty acid composition, and Gujarat Junagadh Soybean-3 (GJS-3) was selected for CRISPR/Cas9-mediated editing of the fatty acid desaturase-2 (FAD2) gene. Agrobacterium-mediated transformation produced 22 regenerated plants, of which 57.1% were PCR-positive for Cas9/sgRNA. Targeted single-nucleotide substitutions were confirmed by Sanger sequencing in three edited lines (T3, T7, and T15), corresponding to an editing efficiency of 13.63%. These lines exhibited a marked increase in oleic acid content (42–45%) compared with the wild type (22%) and a concomitant reduction in linoleic acid (30–32% vs. 54%), resulting in nearly a two-fold improvement in the oleic/linoleic acid ratio. PCR analysis confirmed the absence of Cas9 and U3 sequences, indicating transgene-free edited plants. This study provides the first evidence of CRISPR/Cas9-mediated FAD2 editing in an Indian soybean cultivar and demonstrates its effectiveness in improving oil quality, oxidative stability, and processing efficiency.